A geolocator-tagged fledgling provides first evidence on juvenile movements of Cory's Shearwater Calonectris borealis. Issue 2 (3rd April 2019) - Ramos, Raül; Morera-Pujol, Virginia; Cruz-Flores, Marta; López-Souto, Sofía; Brothers, Michael; González-Solís, Jacob
ABSTRACT: Using geolocator-immersion loggers, we tracked for the first time the migration of one Cory's Shearwater Calonectris borealis fledgling, from its breeding colony in the Canary Islands, and along its first year of life. The juvenile bird initially followed the same migratory path as the adults but visited different areas of the Central and the South Atlantic Ocean.